2016
DOI: 10.20530/ijta_33_119-128
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lipid Profile and Glycemia in Oral Precancerous Lesion and Conditions

Abstract: Background: Lipids are major cell membrane components essential for various biological functions including cell growth and division of normal and malignant tissues. Low lipid values in cancer, precancer lesion and condition may be because of lipid peroxidation as there is greater utilization of lipids including total cholesterol (TC) and triglycerides (TG) for new membrane biogenesis. Cells fulfill these requirements either from circulation or by synthesis through the metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…In the present study, a significant decrease was noticed in serum HDL in the study group of patients as compared to the control group. Similar findings were reported by Mujooet al [33], Anand et al [34], Meisel et al [35], and Granero Fernandez et al [36] in their studies to assess alterations in lipid profile levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, a significant decrease was noticed in serum HDL in the study group of patients as compared to the control group. Similar findings were reported by Mujooet al [33], Anand et al [34], Meisel et al [35], and Granero Fernandez et al [36] in their studies to assess alterations in lipid profile levels.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, serum LDL and serum VLDL levels were significantly lower when compared with the control group, whereas the difference was not statistically significant in the studies done by Mujoo et al [33] and Chalkoo et al [37] While Subbulakshmi et al stated that the decrease in serum LDL and VLDL in squamous cell carcinoma cases may be due to enhanced lipid peroxidation due to decline in antioxidants [38].…”
Section: Discussioncontrasting
confidence: 72%
“…23 In another study, Mujoo et al in another study while comparing lipid levels among cases of OSMF and leukoplakia found the lipid profile of two precancerous lesions to be comparable but found that combined precancerous group had significantly lower TC and TG levels as compared to controls. 24 However, the present study highlighted certain limitations and shortcomings in evaluation of such relationship such as need of a purposive sampling design, adequate number of cases for each type of oral precancerous lesion, histopathological, clinical, demographic, anthropometric and dietary details in order to examine this relationship in a better way. The findings of present study showed that lipid levels in patients with precancerous oral lesions are generally of lower order.…”
Section: Discussionmentioning
confidence: 91%